Randomized controlled trial of overall functional exercise process in perioperative of percutaneous transforaminal endoscopic discectomy. Issue 52 (30th December 2022) - Wang, Shuang; Yu, Hai-Long; Zheng, Liang; Ma, Jun-Xiong; Wang, Hong; Xiang, Liang-Bi; Chen, Yu
Abstract : Background: Percutaneous transforaminal endoscopic discectomy (PTED) has become the standard surgery for the patients of lumbar disc herniation with the advantages of less trauma and rapid recovery. But still some patients have poor prognosis after PTED. A major risk factor associated with the poor prognosis may be the unfit function exercise. Objective: To discuss the effect of overall functional exercise process for PTED. Methods: In January 2019 to June 2020, a single center randomized controlled trial was proceeded. The patients scheduled for PTED were randomly divided into the experimental group, which received overall functional exercise and the control group, which received routine process. The overall process included advance, whole-course exercise and integrating of traditional Chinese medical methods. The general information, visual analog scale (VAS) score and Oswestry Dysfunction Index (ODI) score at each follow-up point perioperative period were compared between the 2 groups. Results: There were no significant differences in the general information, the preoperative VAS and ODI. On the 3rd day after operation, the VAS of low back pain and leg pain in the experimental group were lower than the control group. One month after operation, the VAS of low back pain in the experimental group was lower than that in the control group. One to 3 months after operation, the ODI scores of the experimental group were better than that of the control group. There was no significant difference in modified MacNab index between the experimental group and the control group. Conclusion: Function exercise is important for the prognosis of minimally invasive lumbar surgery. The overall function exercise process perioperative is helpful to relieve the short-term pain of the patients and significantly improve the prognosis.